Evaluación del efecto farmacológico del extracto etanólico de Stryphnodendron adstringens peel sobre el peristalismo intestinal en Mus musculus (Research, Society and Development, 2020)
The objective of this work is to analyze the pharmacological activity of the ethanolic extract of the Barbatimão-verdadeiro in the intestinal peristalsis of mice (Mus Musculus). The study is characterized as a quantitative, exploratory and experimental research, in which two pharmacological tests were performed. The animals (n = 35) were treated with a dose of 500mg / kg Stryphnodendron adstringens ethanolic extract and intestinal motility was evaluated following the intestinal transit models (n = 15) and castor oil-induced diarrhea (n = 20). Statistical analysis with one-way ANOVA and Tukey test for significance analysis showed that the group treated with the plant showed significance in relation to the group treated with loperamide (p